Computer interface display queue based system / Izzatul Afifah Safaruddin - Safaruddin, Izzatul Afifah (2016)
This project is concerned about hours of waiting which cause anxiety, and stress while waiting to be served. Research showed that most of people are waiting for too long in an emergency department. The purpose of this project is to solve this problem and come out with a suitable interface that can positively influence waiting experience. There were two interfaces designed specifically for this purpose. First interface is based on existing interface while second interface is the enhance one. For end product the interfaces is implemented in a web based platform to imitate real world situation. After design and development phase is done, user satisfaction is tested by giving a survey which is based on Questionnaire for User Interface Satisfaction (QUIS). The testing is evaluated by 10 respondents from Jabatan Imigresen Malaysia, Shah Alam. The data is gathered and analyzed and it is proven that the interface can alleviate anxiety and draw users’ attention. Towards the development phase there are some flaws and limitations that can be improve in future studies.